The Adolescent Concept of Social Participation—A Qualitative Study on the Concept of Social Participation from Adolescents with and without Physical Disabilities. (February 2023) - Bärwalde, Tim; Hoffmann, Laura; Fink, Astrid; Völlm, Carina; Martin, Olaf; Bernard, Marie; Gebhard, Britta; Richter, Matthias
Purpose: The construct of social participation is still not clearly defined. To reach a better understanding of social participation, the perspectives of adolescents must be taken into account. This study explores the adolescent concept of social participation and expands knowledge of the meaning of subjective components of the term. Methods: Thirty-four semi-structured interviews were conducted with adolescents with and without physical disabilities or chronic diseases between the ages of 12 and 17 and analyzed according to grounded theory. Results: Adolescents describe social participation as involving reflexive interaction with their social environment. Furthermore, forming a social environment plays an important role. All components of the concept are embedded in a context that influences the ways adolescents participate. Adolescents differentiate between active and passive forms of social participation. The concept of reflexive interaction is situated within an interdependent structure of components such as the "feeling of belonging" and the feeling of "well-being" among adolescents. Conclusion: The results expand the current state of knowledge regarding the theoretical differentiation of social participation by exploring subjective components of the term. This offers the possibility of supplementing the theoretical frameworks of social participation and supports the understanding of the critical importance of social participation for adolescents.